Leaving the day behind: endovascular therapy beyond 24 h in acute stroke of the anterior and posterior circulation - Purrucker, Jan; Ringleb, Peter A.; Seker, Fatih; Potreck, Arne; Nagel, Simon; Schönenberger, Silvia; Berberich, Anne; Neuberger, Ulf; Möhlenbruch, Markus Alfred; Weyland, Charlotte S. (Therapeutic advances in neurological disorders, 2022)
Background:There is little evidence of endovascular therapy (EVT) being performed in acute ischemic stroke beyond 24 h, and that evidence is limited to anterior circulation stroke.Objective:To extend evidence of efficacy and safety of EVT after more than 24?h in both anterior and posterior circulation stroke.Methods:Local, prospectively collected registries were screened for patients with acute ischemic stroke and large-vessel occlusion who had received either EVT?>?24?h after last-seen-well but <24?h after symptom recognition (EVT>24LSW) or EVT?>?24?h since first (definitive) symptom recognition (EVT>24DEF). Patients treated <24?h served as a group for comparison. Favorable outcome was defined as modified Rankin scale (mRS) 0?2 or return to prestroke mRS at 3?months.Results:Between January 2014 and August 2021, N?=?2347 were treated with EVT at our comprehensive stroke center, of whom n?=?43 met the inclusion criteria (EVT>24LSW, n?=?16, EVT>24DEF, n?=?27). EVT>24LSW patients were treated at a median of 28.7?h [interquartile range (IQR)?=?27.3?32.8] after last-seen-well and 7.3?h (IQR?=?2.8?14.3) after symptom recognition; EVT>24DEF patients were treated 52.5?h (IQR?=?26.5?94.2) after first symptoms. Favorable outcome was achieved by 23.3% (10/43) in the EVT?>?24 compared with 39.4% (886/2250) in the EVT??24, 27.9% (12/43) versus EVT??24, 41.7% (5/12) versus EVT?
Gesehen am 03.06.2022